THE APPLICATION OF THE GUIDED INQUIRY LEARNING MODEL ON INDONESIAN LEARNING STUDENTS OF CLASS V SD NEGERI 39 LUBUKLINGGAU - Anerza, Fenia; Prananosa, Ahmad Gawdy; Frima, Aren (Widyagogik, 2022)
This study aims to determine the completion of the Indonesian language learning outcomes for fifth grade students of SD Negeri 39 Lubuklinggau. The research method used is in the form of Pre Experimental Design. The population is the entire fifth grade of SD Negeri 39 Lubuklinggau and at the same time the research sample is 26 students. The data was collected using a test technique consisting of 9 questions. The collected data were analyzed by using t-test. Based on the results of the t-test analysis with a significant level of = 0.05, it was obtained that tcount (4.746) ttable (1.708) Ha was accepted and Ho was rejected, so that it can be concluded that student learning outcomes after participating in Indonesian language learning using the Guided Inquiry model are significantly complete. The average learning outcomes of pre-test (46.65) and post-test (77.51).